2009
DOI: 10.1021/pr900549a
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Lamin A/C Results in Modified Cell Signaling and Metabolism Coupled with Changes in Expression of Structural Proteins

Abstract: Nuclear lamins are intermediate filament proteins that define the shape and stability of nuclei in mammalian cells. In addition to this dominant structural role, recent studies have suggested that the lamin proteins also regulate fundamental aspects of nuclear function. In order to understand different roles played by lamin proteins, we used RNA interference to generate a series of HeLa cell lines to study loss-of-function phenotypes associated with depletion of lamin protein expression. In this study, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Previously reported 2-DE protein profiles of cells depleted of lamin A or expressing laminopathic mutations have revealed 10-50 differentially expressed proteins with identifiable IDs by mass spectral analysis (Chen et al, 2009;Foster et al, 2011;Magagnotti et al, 2012). In our 2-DE analysis of cells expressing GFP-tagged wild-type lamin A or mutant Q294P, 27 proteins could be identified that showed differences in expression.…”
Section: High Throughput Proteomic Analysismentioning
confidence: 63%
See 3 more Smart Citations
“…Previously reported 2-DE protein profiles of cells depleted of lamin A or expressing laminopathic mutations have revealed 10-50 differentially expressed proteins with identifiable IDs by mass spectral analysis (Chen et al, 2009;Foster et al, 2011;Magagnotti et al, 2012). In our 2-DE analysis of cells expressing GFP-tagged wild-type lamin A or mutant Q294P, 27 proteins could be identified that showed differences in expression.…”
Section: High Throughput Proteomic Analysismentioning
confidence: 63%
“…The lamina is linked to the cytoskeleton via interactions with nuclear membrane proteins termed nesprins and SUN (Sad1/ UNC-84 homology) domain proteins and disruption of this linkage can cause defects in nuclear positioning and migration during development (Starr and Han, 2003). Changes in abundance of cytoskeletal proteins have been reported in lamindepleted cells and laminopathic cells (Chen et al, 2009;Foster et al, 2011;Magagnotti et al, 2012). Changes in cytoskeletal organization are likely to affect proteins involved in intracellular transport and signalling, like zymogen granule protein 16B and guanine nucleotide binding protein subunit β2 which were reduced in the mutant cells.…”
Section: Cytoskeletal Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with recent findings, the perturbation to the A549 proteome is relatively slight in response to a lamin KD to ~30% of WT. 47 The perturbation is broader in MSCs in response to a KD of similar magnitude. A breakdown of detectable proteins by function indicates that perturbation to the proteome in MSCs is primarily focused in two areas: upregulation of nuclear proteins (typically proteins involved with mRNA splicing and processing, chromatin binding proteins, and helicases) and downregulation of cytoskeletal and structural proteins (typically actin binding proteins).…”
Section: Proteome Profiling Following Lamin Kd In A549 and Mscsmentioning
confidence: 96%